2006
DOI: 10.1016/j.socscimed.2006.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Taking ad-Vantage of lax advertising regulation in the USA and Canada: Reassuring and distracting health-concerned smokers

Abstract: We explored the evolution from cigarette product attributes to psychosocial needs in advertising campaigns for low-tar cigarettes. Analysis of previously secret tobacco industry documents and print advertising images indicated that low-tar brands targeted smokers who were concerned about their health with advertising images intended to distract them from the health hazards of smoking. Advertising first emphasized product characteristics (filtration, low tar) that implied health benefits. Over time, advertising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…The tobacco industry tailors its advertising and product design to certain populations using imagery or creating desired feelings by those populations (Anderson, Pollay, & Ling, 2006). E-cigarette companies are using similar advertising and promotional strategies to aggressively market their products (Felberbaum, 2013).…”
Section: Electronic Cigarettes and Advertisingmentioning
confidence: 99%
“…The tobacco industry tailors its advertising and product design to certain populations using imagery or creating desired feelings by those populations (Anderson, Pollay, & Ling, 2006). E-cigarette companies are using similar advertising and promotional strategies to aggressively market their products (Felberbaum, 2013).…”
Section: Electronic Cigarettes and Advertisingmentioning
confidence: 99%
“…These challenges necessitated a move away from explicit health messages and towards other messages that would appeal to different groups of potential consumers of ‘low-tar’ or ‘light’ tobacco products. Research has elucidated many of these alternative marketing messages for ‘low-tar’ and ‘light’ cigarettes,4 15 and has demonstrated that consumers tend to perceive ‘low-tar’ and ‘light’ cigarettes to be less harmful than ‘regular’ cigarettes 16–20. less is understood about messages for menthol cigarettes or about how consumers perceive menthol.…”
Section: Introductionmentioning
confidence: 99%
“…In Western countries, “light” and “low tar” cigarettes were initially introduced in the 1960s and 1970s as smokers became aware of the health risks of smoking. These cigarettes have been marketed using advertising and packaging which suggests that these brands are less harmful alternatives to “full flavour” or “regular” brands4 5 and therefore appeal to health concerned smokers 6–9. Consequently, the availability of “low tar” cigarettes is likely to have discouraged some smokers from quitting,10 11 although this evidence is not conclusive 12.…”
mentioning
confidence: 99%